Reckless grace : the gift. the mystery. the embrace - Vanderbush, Bill; Eaton, Brit (Savage, Minnesota, U.S. ; Broadstreet Publishing Group, LLC, 2020)
Grace is the ultimate expression of love. We all know we need grace and forgiveness, but why is it so difficult to extend them to ourselves and others? In Reckless Grace, Bill Vanderbush and Brit Eaton challenge our understanding of forgiveness with powerful biblical evidence and show us how to step into the fullness of grace, bringing reconciliation and restoration to our relationships using: - practical steps and accessible tools to help identify and overcome barriers to grace - carefully crafted exercises and reflections that explore past and present hurts and work toward healing - gentle guidance in becoming gospel-centered and releasing grace into a fallen world. God isn't reckless, but the way he extends grace defies all reason. We can learn to freely give what we have been freely gifted
Keywords: Christian life; Grace (Theology)